Biology, sociology, geology by computational physicists - Stauffer, Dietrich; Oliveira, Suzana Moss de, 1955- (Monograph series on nonlinear science and complexity, 2006)
The book requires only rudimentary physics knowledge but ability to program computers creatively and to keep the mind open to simple and not so simple models, based in individuals, for the living world around us. * Interdisciplinary coverage * Research oriented * Contains and explains programs * Based on recent discoveries * Little special knowledge required besides programming * Suitable for undergraduate and graduate research projects.